A case of active incomplete biliary cirrhosis in an aged female Japanese macaque (Macaca fuscata). Issue 4 (4th May 2018) - Ryu, Bokyeong; Eo, Kyung‐Yeon; Jang, Ja‐Jun; Kim, C‐Yoon; Lee, Ji Min; Oh, Hanseul; Kim, Ukjin; Kim, Jin; Lee, Hyun‐Ho; Jung, Young‐Mok; Park, Jae‐Hak
Abstract: We describe the first case of biliary cirrhosis in Japanese macaque. Clinical signs had not been detected. The liver was nodular. Histopathologically, portal‐to‐portal pattern of fibrosis might have indicated chronic cholestasis. Fibrotic septa were infiltrated with inflammatory cells. Therefore, this case could be diagnosed as active incomplete biliary cirrhosis.